Comment: Systematic Interest-Rate Risk in a Two-Index Model of Returns - Korkie, Bob M. (Journal of Financial and Quantitative Analysis, 1974)
Bernell Stone's paper extends the single-factor market model to a two-factor model to “better” explain the stochastic process that generates security returns. The inductive search for new models (of which his paper is one) presumably is predicated upon some unsatisfactory results of joint tests of the single-index market model and the capital asset pricing model. It is well known that there are other components of systematic or covariance risk that are not explained by the single-market factor. In the most general sense then, one would conclude that the truth of the return generating process is a multiple factor model, given that the process is indeed linear in the factors. Professor Stone chooses a two-factor (or index) model, in which the known factors are: (1) the return on an equity index, and (2) the return on a bond index. To this extent his interesting work is a special case of the more general work of others.